Mobile Apps to improve therapy: the health practitioner in your pocket knows you - Madeira, Rui Neves (2018)
Comunicação apresentada no 15th International Conference on Advances in Mobile Computing & Multimedia (MoMM2017), 04-06 December 2017, Salzburg, Austria